In which order should verbal prefixation in Croatian as L2 be taught? - Udier, Sanda Lucija (Vestnik za tuje jezike, 2017)
Teaching verbal prefixation in the context of Croatian as a second language (CL2) has been receiving an increasing amount of attention recently, and one of the questions which has come up has to do with the order in which verbal prefixation should be taught for the teaching to be more effective. To answer this question, this research, conducted among CL2 learners at the B2 and C1 levels of language proficiency, tests the hypothesis that an understanding of the meaning of a verbal prefix is strongly supported by understanding the meaning of its cognate preposition and directly related to whether a verbal prefix co-occurs with its cognate preposition when a prefixed verb is used in a sentence. Based on the research results conclusions were drawn on the order in which the teaching of verbal prefixation in the CL2 classroom should progress.
Keywords: Croatian; hrvaščina; tuji jeziki; foreign languages; glagol; verb; verbal prefixes; glagolske predpone; didaktika jezika; language didactics